Analisis Kimia Ikan Ekor Kuning Asap Industri Rumah Tangga di Kota Jayapura - Kristina Haryati; Nurlita Dianingsih (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Fish is highly susceptible to deterioration without any preservative or processing measures and requires proper handling and preservation to increase its shelf life. Smoked fish is traditionally processed by fish through an open process of hot smoked. Smoked fish process in Indonesia, especially in Papua, is still carried out traditionally with capital and small business scale so that the use of tools is still simple. The aim of this research was to study the proximate composition of smoked yellowfin fish, which were taken from different producers in Youtefa Market, Jayapura City, Papua. The analysis on smoked yellowfin fish applied of proximate analysis (moisture level, ash level, fat level, and protein level). The result of this research showed that the highest moisture level was EK.K sample with 67.17%. The highest value of ash level was EK.T1 sample with 8.15%. The highest of fat and protein level were EK.K sample, with 18.63% and 6.42%, respectively. Key words: Smoked yellowfin, proximate analysis.